Anisochilus kanyakumariensis (Lamiaceae): a new species from the Western Ghats, India - Shinoj, Kalathummarath; Sunojkumar, Purayidathkandy (Phytotaxa, 2018)
A new species, Anisochilus propecephalus (Lamiaceae) from Kanyakumari, Western Ghats, India is described and illustrated here. This new species is similar to Anisochilus carnosus  in vegetative characters and inflorescence nature  whereas in  floral characters it is close to Anisochilus paniculatus, but differs from both by its decumbent  habit, leaf size and shape, short petiole, inflorescence nature, size and shape of spike head, corolla size and shape  and  densely villous calyx. Detailed description, photographs, illustrations, IUCN red list category, distribution map, notes on biogeography and other relevant notes are provided.